1937
DOI: 10.1002/j.1538-7305.1937.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Coaxial and Balanced Transmission Lines in Filters and Wide-Band Transformers for High Radio Frequencies

Abstract: At the high radio frequencies, filters and transformers become difficult to construct from conventional electrical coils and condensers, on account of the small sizes of the elements, the large effects of the interconnecting windings and the low ratios of reactance to resistance realizable in coils. It is shown in this paper that selective filters and wide‐band transformers can be constructed using transmission lines and condensers as elements. The ratio of reactance to resistance in these elements can be made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Studies on microwave filters started before World War II. The first study was reported in 1937 by W.P Mason and R.A. Sykes [1]. Although the study was conducted almost 85 years ago, the outcomes are still applicable today.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on microwave filters started before World War II. The first study was reported in 1937 by W.P Mason and R.A. Sykes [1]. Although the study was conducted almost 85 years ago, the outcomes are still applicable today.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the military desired this technology to be used in radar, band limiting, multiplexing, and electronic counter measures on their attempt to step up from the analogue lumped filters used at the beginning of WWII. The Radio Research Laboratory did much of the early work on band-pass distributed impedance filter to develop coaxial filters for electronic countermeasure applications [7]. Telecommunication companies and other organizations with large data networks applied the microwave filters to their data broadcasting [8].…”
Section: Introductionmentioning
confidence: 99%
“…Coaxial transformers are normally used in high-frequency radio applications because it confines the flux leakage inside of the transformer windings [1]. However, it is also possible to find some applications on the power electronics field [2] [3].…”
Section: Introductionmentioning
confidence: 99%